2005
DOI: 10.1039/b414649b
|View full text |Cite
|
Sign up to set email alerts
|

Discotic liquid crystals stabilized by interionic interactions: imidazolium ion-anchored paraffinic triphenylene

Abstract: Incorporation of imidazolium ion functionalities into the paraffinic side-chain termini of a triphenylene derivative resulted in stabilization of a columnar mesophase of its liquid crystalline assembly, which was retained over a wider temperature range down to 4 degrees C by an externally added imidazolium-based ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 15 publications
6
44
0
5
Order By: Relevance
“…[254] oder ein (167 b) oder sechs Imidazoliumionen (168) angeknüpft werden. [255,256] Diese Triphenylensalze waren mesomorph und zeigten columnare Mesophasen (Schema 70).…”
Section: Columnare Mesophasen Auf Basis Von Wasserstoffbrückenunclassified
“…[254] oder ein (167 b) oder sechs Imidazoliumionen (168) angeknüpft werden. [255,256] Diese Triphenylensalze waren mesomorph und zeigten columnare Mesophasen (Schema 70).…”
Section: Columnare Mesophasen Auf Basis Von Wasserstoffbrückenunclassified
“…In 2005, we reported that 1 10 forms an LC assembly with a Col h geometry. 6 The phase sequence upon cooling displayed, after the Col h mesophase (111-47°C), an optically isotropic phase, which however was unidentifiable due to no clear diffractions with our conventional diffractometer for X-ray analysis (XRD). Quite recently, we reinvestigated the phase diagram of 1 10 using a synchrotron radiation beam and found that the optically isotropic phase is not amorphous but an LC mesophase with a Cub bi geometry ( Figure 1b).…”
mentioning
confidence: 99%
“…66 observation is outstanding because paraffinic TP 6 ( Figure 18) without imidazolium ion functionalities has been reported to form a columnar mesophase only in a much narrower temperature range (58-69 C). 67 Interestingly, upon mixing with an equimolar amount of 1-hexyl-3-methylimidazolium tetrafluoroborate (HMIBF 4 , Figure 2), the temperature range of the columnar LC phase is significantly expanded from 47-111 to 4-117 C (Figures 19b and 20b).…”
Section: Stabilization Of One-dimensional Columnar Assembly By Interimentioning
confidence: 96%